Comprehensive Succinylome Profiling Reveals the Pivotal Role of Lysine Succinylation in Energy Metabolism and Quorum Sensing of Staphylococcus epidermidis - Zhao, Yiping; Han, Yang; Sun, Yuzhe; Wei, Zhendong; Chen, Jialong; Niu, Xueli; An, Qian; Zhang, Li; Qi, Ruiqun; Gao, Xinghua (Frontiers in Microbiology, 2021)
Background: Lysine succinylation is a newly identified PTM, which exists widely from prokaryotes to eukaryotes and participates in various cellular processes, especially in the metabolic processes. Staphylococcus epidermidis is a commensal bacterium in the skin, which attracts more attention as a pathogen, especially in immunocompromised patients and neonates by attaching to medical devices and forming biofilms. However, the significance of lysine succinylation in proteins of Staphylococcus epidermidis has not been investigated. Objectives: The purpose of this study was to investigate the physiological and pathological processes of Staphylococcus epidermidis at the level of post-translational modification. Moreover, by analyzing previous succinylome datasets in various organisms, we tried to provide in-depth understanding of lysine succinylation. Methods: Using antibody affinity enrichment followed by LC-MS/MS analysis, we examined the succinylome of Staphylococcus epidermidis (ATCC®12228™). Then, bioinformatics analysis was performed, including Gene Ontology, KEGG enrichment, motif characterization, secondary structure, protein-protein interaction, and BLAST analysis. Results: A total of 1557 succinylated lysine sites in 649 proteins were identified in Staphylococcus epidermidis (ATCC 12228). Among these succinylation proteins, GO annotation showed that proteins related to metabolic processes accounted for the most. KEGG pathway characterization indicated that proteins associated with the glycolysis/ gluconeogenesis and citrate cycle (TCA cycle) pathway were more likely to be succinylated. Moreover, 13 conserved motifs were identified. The specific motif KsuD was conserved in model prokaryotes and eukaryotes. Succinylated proteins with this motif were highly enriched in the glycolysis/gluconeogenesis pathway. One succinylation site(K144) was identified in S-ribosylhomocysteine lyase, a key enzyme in the quorum-sensing system, indicating the regulatory role succinylation may play in bacterial processes. Furthermore, 15 succinyltransferases and 18 desuccinylases(erasers) were predicted in S.epidermidis by BLAST analysis. Conclusions: We performed the first comprehensive profile of succinylation in Staphylococcus epidermidis and illustrated the significant role succinylation may play in energy metabolism, QS system, and other bacterial behaviors. This study may be a fundamental basis to investigate the underlying mechanisms of colonization, virulence, and infection of S. epidermidis, as well as provide a new insight into regulatory effects succinylation may lay on metabolic processes. (Data are available via ProteomeXchange with identifier PXD022866).